Assessing the Short-Term Impact of the Oak Lace Bug (Corythucha arcuata) on Growth and Wood Properties of Quercus frainetto - Angelos Tsikas; Paraskevi Karanikola (South-East European Forestry, 2025)
The oak lace bug Corythucha arcuata (Say, 1832), an invasive sap-sucking insect originating from North America, has rapidly spread across Europe, raising concerns about its impact on oak forest ecosystems. This study evaluates the short-term effects of C. arcuata infestation on radial growth and wood properties of Hungarian oak Quercus frainetto Ten. in Kalyvas-Margaritiou public forest complex along the Xanthi-Drama national highway in northeastern Greece, Xanthi Prefecture, Eastern Macedonia and Thrace, Greece. Oak trees were sampled in areas with varying degrees of infestation to compare growth characteristics and evaluate potential physiological impacts. Results revealed no statistically significant differences in tree radial growth or late/early wood ratios (p=0.125 and p=0.0837, respectively) between infested and non-infested trees. The study also highlights the critical role of highways as dispersal corridors, with infestation levels decreasing with distance from the roads. While short-term impacts appear negligible, the potential for long-term consequences remains a concern. Continuous infestation could interact with other stressors, such as drought, defoliation, and climate extremes, posing risks to tree health, acorn production, and associated biodiversity. This study underscores the importance of monitoring invasive species and their cumulative impacts on forest ecosystems.